Primary Cell Cultures for Understanding Rat Epididymal Inflammation. (10th July 2014) - Chapin, Robert E.; Winton, Timothy R.; Nowland, William S.; Kumpf, Steven W.; Davenport, Scott; Karanian, David; Streck, Randal D.; Coskran, Timothy M.; Barbacci‐Tobin, Elsa G.; Houle, Christopher; Campion, Sarah N.
<x xml:space="preserve">Abstract</x> Treatment‐induced epididymal inflammation and granuloma formation is only an occasional problem in preclinical drug development, but it can effectively terminate the development of that candidate molecule. Screening for backup molecules without that toxicity must be performed in animals (generally rats) that requires at least 2 to 3 weeks of in vivo exposure, a great deal of specially synthesized candidate compound, and histologic examination of the target tissues. We instead hypothesized that these treatments induced proinflammatory gene expression, and so used mixed‐cell cultures from the rat epididymal tubule to monitor the induction of proinflammatory cytokines. Cells were exposed for 24 hr and then cytotoxicity was evaluated with the MTS assay and mRNA levels of Interleukin‐6 (IL‐6) and growth‐related oncogene (GRO) were measured. We found that compounds that were more toxic in vivo stimulated a greater induction of IL‐6 and GRO mRNA levels in vitro. By relating effective concentrations in vitro with the predicted Ceff, we could rank compounds by their propensity to induce inflammation in rats in vivo. This method allowed the identification of several compounds with very low inflammatory induction in vitro. When tested in rats, the compounds produced small degrees of inflammation at an acceptable margin (approximately 20×), and have progressed into further development